Male reproductive ageing arises via multifaceted mating-dependent sperm and seminal proteome declines, but is postponable in Drosophila - Sepil, I (University of Oxford, 2020)
These 12 datasets were collected and analysed as part of the paper 'Male reproductive ageing arises via multifaceted mating-dependent sperm and seminal proteome declines, but is postponable in Drosophila'. The datasets give: female egg laying data; insulin mutant proportion alive data; insulin mutant reproduction data; male accessory gland sperm viability data; male cyst number data; male proportion alive data; male reproduction data; male seminal vesicle and accessory gland size data; male seminal vesicle sperm viability data; number of sperm in female storage data; tudor egg laying data; tudor remating data.